DESIGN OF A TRI-BAND WEARABLE ANTENNA FOR MILLIMETER-WAVE 5G APPLICATIONS - Ahmad, Sarosh; Boubakar, Hichem; Naseer, Salman; Alimin, Mohammad Ehsanul; Sheikh, Yawar Ali; Ghaffar, Adnan; AL-GBURI, AHMED JAMAL ABDULLAH; Parchin, Naser Ojaroudi (MDPI, 2022)
A printed monopole antenna for millimeter-wave applications in the 5G frequency region is described in this research. As a result, the proposed antenna resonates in three frequency bands that are designated for 5G communication systems, including 28 GHz, 38 GHz, and 60 GHz (V band). For the sake of compactness, the coplanar waveguide (CPW) method is used. The overall size of the proposed tri-band antenna is 4 mm × 3 mm × 0.25 mm. Using a watch strap and human tissue, such as skin, the proposed antenna gives steady results. At 28 GHz, 38 GHz, and 60 GHz, the antenna’s gain is found to be 5.29 dB, 7.47 dB, and 9 dB, respectively. The overall simulated radiation efficiency is found to be 85% over the watch strap. Wearable devices are a great fit for the proposed tri-band antenna. The antenna prototype was built and tested in order to verify its performance. It can be observed that the simulated and measured results are in close contact. According to our comparative research, the proposed antenna is a good choice for smart 5G devices because of its small size and simple structure, as well as its high gain and radiation efficiency.